2008
DOI: 10.2166/wh.2009.122
|View full text |Cite
|
Sign up to set email alerts
|

A sea change ahead for recreational water quality criteria

Abstract: The United States Environmental Protection Agency is committed to developing new recreational water quality criteria for coastal waters by 2012 to provide increased protection to swimmers.We review the uncertainties and shortcomings of the current recreational water quality criteria, describe critical research needs for the development of new criteria, as well as recommend a path forward for new criteria development. We believe that among the most needed research needs are the completion of epidemiology studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
139
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 47 publications
(22 reference statements)
1
139
1
4
Order By: Relevance
“…The U.S. Environmental Protection Agency currently recommends the use of E. coli and enterococci as indicator organisms for the assessment of recreational water quality (2, 50). Many questions have been raised about the validity of the FIB paradigm for predicting human health risks (7,52,53), and the effects of environmental factors on survival of FIB and pathogens need to be systematically investigated in order to chart a clear course for development of the next generation of tools for water quality assessment. The data presented here on E. coli survival show significant effects of the natural microbiota, water type, and matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Environmental Protection Agency currently recommends the use of E. coli and enterococci as indicator organisms for the assessment of recreational water quality (2, 50). Many questions have been raised about the validity of the FIB paradigm for predicting human health risks (7,52,53), and the effects of environmental factors on survival of FIB and pathogens need to be systematically investigated in order to chart a clear course for development of the next generation of tools for water quality assessment. The data presented here on E. coli survival show significant effects of the natural microbiota, water type, and matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies conducted in a subtropical environment, such as that of South Florida, where this study was conducted, have repeatedly shown the limited accuracy of indicator microbe standards for determining the presence of pathogens (27,35). This lack of correlation is understandable since an indicator microbe, such as enterococci, may come from relatively low-risk sources of fecal pollution and therefore may not be related to human or other high-risk sources of fecal pollution and pathogens (9). It has also been shown in both subtropical and temperate climates that indicator bacteria can multiply in the environment, resulting in a false impression of increased microbial pollution and pathogen presence (4,7,19,24,41,45,57,58).…”
mentioning
confidence: 90%
“…aterborne pathogens pose a health risk to recreational water users (1), in drinking water systems (2), and in aquatic organisms such as shellfish that are consumed by humans (3). These waterborne pathogens include more than 40 different groups or genera, including viruses, bacteria, protozoa, cyanobacteria, and helminths (4).…”
mentioning
confidence: 99%